Web-Based Learning: Size matters - Williams, Peter (Proceedings of the International Conference on Networked Learning, 2000)
This paper considers some issues related to a web-based vocational course in management for small businesses. Aspects of size are examined: the size of the working groups, the size of the course units and the scale of the support infrastructure needed. These aspects appear to have had an important bearing upon the targeting of course materials to clients and upon client retention. On the basis of this experience plans are outlined which aim to improve the effectiveness of client-client and tutor-client communication and to make the course attractive and useful to a wider market.